2016
DOI: 10.1111/ejh.12713
|View full text |Cite
|
Sign up to set email alerts
|

The ability of multipotent mesenchymal stromal cells from the bone marrow of patients with leukemia to maintain normal hematopoietic progenitor cells

Abstract: The ability of patients' MSCs to maintain normal hematopoietic progenitor cells was shown to change in comparison with MSCs from healthy donors and depended on nosology. During treatment, the functional capacity of patients' MSCs had been partially restored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Genes associated with quiescence and survival of stem/progenitor cells were increased such as ANGP51, SPP1, and SDF-1α [7]. Others have shown that AML-MSCs vs. ND-MSCs had decreased ability to support normal cobblestone area forming cells [56]. Other groups found no difference between AML-MSCs and ND-MSCs to support normal hematopoiesis in vitro [57].…”
Section: Discussionmentioning
confidence: 98%
“…Genes associated with quiescence and survival of stem/progenitor cells were increased such as ANGP51, SPP1, and SDF-1α [7]. Others have shown that AML-MSCs vs. ND-MSCs had decreased ability to support normal cobblestone area forming cells [56]. Other groups found no difference between AML-MSCs and ND-MSCs to support normal hematopoiesis in vitro [57].…”
Section: Discussionmentioning
confidence: 98%
“…Their putative role in oncogenesis and leukemogenesis has not been fully clarified and the results from the studies already published are contradictory. In vitro studies have shown that MSCs from newly diagnosed adult patients with leukemia (acute myeloid leukemia and acute lymphoblastic leukemia) are less efficient for supporting normal hematopoietic progenitor cell survival and this functional capacity is partially restored after chemotherapy [ 5 ]. Their implication in childhood ALL has only recently being addressed, revealing that ALL-MSCs display reduced proliferative capacity and ability to support long-term hematopoiesis in vitro while those isolated at diagnosis did not differ from those obtained during treatment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a malignant context, and more particularly in acute myeloid leukemia (AML), the most recent studies report functional abnormalities of human MSCs, which have a significant impact on the aggressiveness of the disease. Among these anomalies, growth deficiency, altered osteogenic differentiation ability and reduced capacity to support hematopoietic cells (26)(27)(28)(29)(30)(31) have been described, as well as modifications of the secretome (28,32), which induce in vivo shaping of the stromal niche by leukemic cells (33). Moreover, single cell analyses of murine BM stromal cells recently revealed that leukemia remodels the BM stroma to the disadvantage of normal hematopoietic cells.…”
Section: Heterogeneity Of Cafs/mscsmentioning
confidence: 99%